Optimal NaCl Medium Enhances Squalene Accumulation in Thraustochytrium sp. ATCC 26185 and Influences the Expression Levels of Key Metabolic Genes - Zhang, Aiqing; He, Yaodong; Sen, Biswarup; Wang, Weijun; Wang, Xin; Wang, Guangyi (Frontiers in Microbiology, 2022)
Squalene, a natural lipid of the terpenoid family, is well-recognized for its roles in regulating cholesterol metabolism, preventing tumor development, and improving immunity. Among plant and other sources, the unicellular marine protists—thraustochytrids—have shown great potential for large-scale squalene production. However, salt stress is known to influence the growth of thraustochytrids, which can eventually affect the squalene content. Here, we study the effects of an optimal concentration of NaCl on the squalene content and transcriptome of Thraustochytrium sp. ATCC 26185. Under the optimal culture conditions (glucose, 30 g/L; yeast extract, 2.5 g/L; NaCl, 5 g/L; 28 °C), the strain yielded 67.7 mg squalene/g cell dry weight, which was significantly greater than that (5.37 mg/g) under the unoptimized conditions. NaCl was determined as the most significant (R = 135.24) factor for squalene production among glucose, yeast extract, and NaCl. Further comparative transcriptomics between the ATCC 26185 culture with and without NaCl addition revealed that NaCl (5 g/L) influences the expression of certain key metabolic genes, namely, IDI, FAS-, FAS-, ALDH3, GS, and NDUFS4. The differential expression of these genes possibly influenced the acetyl-CoA and glutamate metabolism and resulted in an increased squalene production. Through the integration of bioprocess technology and transcriptomics, this report provides the first evidence of the possible mechanisms underscoring increased squalene production by NaCl.